Chapter The environmental function analysis: a promising tool to evaluate the coastal zone conservation potential - Giordano, Laura (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study reports and compares the application and usefulness of the Environmental Function Analysis to discover the potential for conservation of two very different coastal areas located along the Campania Region (Southern Italy). The first EFA site is located in the Volturno River Coastal Zone (southern Tyrrhenian sea) while the second EFA study site is located at the western end of the Sorrento Peninsula in the Bay of Naples. Results demonstrated that EFA permits to effectively synthetize the information on coastal system functioning and on their potential for conservation or development.